Antiobesity and antihyperglycaemic effects of Adiantum capillus-veneris extracts: in vitro and in vivo evaluations - Violet Kasabri; Entisar K Al-Hallaq; Yasser K Bustanji; Khalid K Abdul-Razzak; Ismail F Abaza; Fatma U Afifi (Taylor & Francis Group, 2017)
Context: Adiantum capillus-veneris L. (Adiantaceae) hypocholesterolemic activity is therapeutically praised. Objectives: Pharmacological modulation of pancreatic triacylglycerol lipase (PL) and α-amylase/α-glucosidase by A. capillus-veneris are evaluated. Materials and methods: Using positive controls (acarbose, orlistat, guar gum, atorvastatin, glipizide and metformin) as appropriate, crude aqueous extracts (AEs) of A. capillus-veneris aerial parts were tested via a combination of in vitro enzymatic (0.24-100 mg/mL), acute in vivo carbohydrate tolerance tests (125, 250 or 500 mg/kg body weight [b.wt]) and chronic in vivo studies (500 mg/kg b.wt) in high cholesterol diet (HCD) fed Wistar rats. Results: Like acarbose, A. capillus-veneris as well as chlorogenic acid, with respective IC50 values (mg/mL) of 0.8 ± 0.0 and 0.2 ± 0.0, were identified as in vitro potent dual inhibitors of α-amylase/α-glucosidase. Unlike guar gum, A. capillus-veneris had no glucose diffusion hindrance capacity. Equivalent to orlistat, A. capillus-veneris and its phytoconstituents inhibited PL in vitro with an ascending order of PL- IC50 values (μg/mL): ferulic acid; 0.48 ± 0.06 < ellagic acid; 13.53 ± 1.83 < chlorogenic acid; 38.4 ± 2.8 < A. capillus-veneris; 1600 ± 100. Incomparable to acarbose or metformin and glipizide, A. capillus-veneris (125, 250 and 500 mg/kg b.wt) lacked antihyperglycaemic efficacies in acute starch- or glucose-evoked postprandial hyperglycaemia increments in normoglycaemic overnight fasting rats. Superior to atorvastatin; A. capillus-veneris exerted significant antiobesity (p < 0.001) with marked triacylglycerol-reducing capacities (p < 0.001) in comparison to rats fed with HCD for 10 weeks. Discussion and conclusion: A. capillus-veneris, modulating pancreatic digestive enzymes, may be advocated as a combinatorial diabesity prevention/phytotherapy agent.